Comparative analysis on online marketing, BRAC EPL Stock Brokerage Limited - Moeen, Enzemam Ali (BRAC University, 2016)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2016.